2000
DOI: 10.1080/10810730050019555
|View full text |Cite
|
Sign up to set email alerts
|

Coping in Cyberspace: The Impact of Internet Use on the Ability of HIV-Positive Individuals to Deal with Their Illness

Abstract: The human immunodeficiency virus (HIV) poses one of the greatest health threats of modern times. The Internet provides unparalleled access to resources that can assist individuals coping with HIV infection. Despite the promise of online resources to help individuals manage and cope with their illness, few studies have investigated the impact of their use. Those that have looked primarily at Internet use from a group perspective. These studies were usually "bounded" as well, focusing on electronic support group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 0 publications
1
59
0
2
Order By: Relevance
“…Some studies have suggested a survival benefit for cancer patients as well, although this finding is controversial. David Spiegel appropriately comments, "Curing cancer may not be a question of mind over matter, but mind does matter" [33]. Group therapy is typically underutilized because many patients have difficulties attending due to transportation or cultural barriers.…”
Section: Community Building and Supportmentioning
confidence: 99%
“…Some studies have suggested a survival benefit for cancer patients as well, although this finding is controversial. David Spiegel appropriately comments, "Curing cancer may not be a question of mind over matter, but mind does matter" [33]. Group therapy is typically underutilized because many patients have difficulties attending due to transportation or cultural barriers.…”
Section: Community Building and Supportmentioning
confidence: 99%
“…Such spaces provide a communication channel for interaction between people facing the same or a similar situation. Several research studies report the benefits of such social support (Reeves, 2000;Eysenbach et al, 2004) that can complement or even replace traditional patient support groups. Participants share technical information about new treatments, discuss their experiences, and encourage each other.…”
Section: Exchangementioning
confidence: 99%
“…It is argued that information might make a difference in coping with HIV/AIDS (Kalichman, 2007;Kalichman et al, 2003Kalichman et al, , 2005Kalichman et al, , 2006bMo & Coulson, 2008;Reeves, 2000Reeves, , 2001, in the prevention and reduction of HIV/AIDS (Albright & Kawooya, 2005;Blumberg, 2000), motivation to adhere to treatment (Cornman, Schmiege, Bryan, Benziger, & Fisher, 2007;Johnson & Case, 2012), motivation to change sexual behavior (Fisher, 2012), and in promoting HIV testing (Davis et al, 2011). Substantial interest is reported in use of the Internet as tool for information seeking and for delivering educational interventions, as well as for information dissemination and supporting people in coping with HIV/AIDS (Kalichman, 2007;Kalichman, Weinhardt, Benotsch, & Cherry, 2002;Kalichman et al, 2003Kalichman et al, , 2005Kalichman et al, , 2006aKalichman et al, , 2006bKalichman et al, , 2012Kalichman, Picciano, & Roffman, 2008;Mayben & Giordano, 2007;Mo & Colson, 2008;Reeves, 2000;Rice, Monro, Barman-Adhikari, & Young, 2010;Robinson & Graham, 2010;…”
Section: Introductionmentioning
confidence: 99%
“…Substantial interest is reported in use of the Internet as tool for information seeking and for delivering educational interventions, as well as for information dissemination and supporting people in coping with HIV/AIDS (Kalichman, 2007;Kalichman, Weinhardt, Benotsch, & Cherry, 2002;Kalichman et al, 2003Kalichman et al, , 2005Kalichman et al, , 2006aKalichman et al, , 2006bKalichman et al, , 2012Kalichman, Picciano, & Roffman, 2008;Mayben & Giordano, 2007;Mo & Colson, 2008;Reeves, 2000;Rice, Monro, Barman-Adhikari, & Young, 2010;Robinson & Graham, 2010;…”
Section: Introductionmentioning
confidence: 99%